Engineering SnO2 nanorods/ethylenediamine-modified graphene heterojunctions with selective adsorption and electronic structure modulation for ultrasensitive room-temperature NO2 detection. (25th January 2021) - Zheng, Shengliang; Sun, Jianyong; Hao, Juanyuan; Sun, Quan; Wan, Peng; Li, Yue; Zhou, Xin; Yuan, Ye; Zhang, Xu; Wang, You
Abstract: Ever-increasing concerns over air quality and the newly emerged internet of things (IoT) for future environmental monitoring are stimulating the development of ultrasensitive room-temperature gas sensors, especially for nitrogen dioxide (NO2 ), one of the most harmful air pollution species released round-the-clock from power plants and vehicle exhausts. Herein, tin dioxide nanorods/ethylenediamine-modified reduced graphene oxide (SnO2 /EDA-rGO) heterojunctions with selective adsorption and electronic structure modulation were engineered for highly sensitive and selective detection of NO2 at room temperature. The modified EDA groups not only enable selective adsorption to significantly enrich NO2 molecules around the interface but also realize a favorable modulation of SnO2 /EDA-rGO electronic structure by increasing the Fermi level of rGO, through which the sensing performance of NO2 is synergistically enhanced. The response of the SnO2 /EDA-rGO sensor toward 1 ppm NO2 reaches 282%, which exceeds the corresponding SnO2 /rGO sensor by a factor of 2.8. It also exhibits a low detection limit down to 100 ppb, enhanced selectivity, and rapid response/recovery kinetics. This approach to designing a novel heterojunction with significantly enhanced chemical and electric effects may shed light on the future engineering of gas-sensing materials.